Cultivating Porang Plants (Amorphophallus Oncophyllus Prain) Using Agroforestry Patterns: Maintaining Ethnoscience in North Lombok Regency - Joko Triwanto; Amir Syarifudin; Zaodan Faqih; Zulharman Zulharman (Postgraduate, University of Mataram, 2023)
Management of community forests using an agroforestry pattern based on porang (Amorphophallus oncophyllus Prain) plants can increase community income. Porang is a tuber plant from tropical areas that belongs to the potential Araceae family, but its product has yet to be well known. The research objective is to analyze the potential of the porang plant (A. oncophyllus Prain) on farmers' income. The benefit of this research is information for the people of North Lombok on the sustainable cultivation of porang plants and, simultaneously, maintaining local science in the region. The research method uses qualitative descriptions through observation/interviews with porang farmer respondents in Rempek Darussalam Village, North Lombok. The research results show that cultivating porang plants with agroforestry can be sustainable. The porang plant as local wisdom in North Lombok is also an effort to maintain local scientific or ethnoscience. The research results also show the economic potential for porang farmers. The average income of porang farmers is 64,927,885 (IDR) /year/hectare. A viable porang farming business planted under the stands of sengon (Falcataria mulucana (L) and can contribute to an income R/C Ratio of 8.11%.